Collaborative Strategies in Learning Tor-Tor Dance - Diah Ayu Putri Anggraini; Heni Komalasari; Fitri Kurniati (Journal of Dance and Dance Education Studies, 2025)
This study aims to determine the level of student learning outcomes before and after the implementation of a collaborative strategy in dance classes at SMPN 1 Kunduran. To achieve optimal learning outcomes, appropriate teaching strategies are essential. At SMPN 1 Kunduran, the effectiveness of dance education has faced challenges, as reflected in the low student performance. This issue stems from a one-way teaching method that limits students' opportunities for exploration and focuses mainly on memorization and imitation of movements. The research was conducted using a quantitative approach, employing an experimental method to evaluate the impact of collaborative strategies on student learning outcomes. The findings indicate that the implementation of collaborative strategies in dance education at SMPN 1 Kunduran has proven effective. There was a significant improvement in students' learning outcomes, covering cognitive, affective, and psychomotor aspects. These results highlight the importance of adopting more interactive and collaborative teaching methods. Based on these findings, collaborative strategies are worth considering as an effective approach to enhancing the quality of education, particularly in art subjects such as dance. In dance education, student interaction and active participation are crucial to achieving optimal learning outcomes.